2013
DOI: 10.1007/s11357-013-9603-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the mammalian gastrointestinal tract: a complex organ system

Abstract: Gastrointestinal disorders are a major cause of morbidity in the elderly population. The gastrointestinal tract is the most complex organ system; its diverse cells perform a range of functions essential to life, not only secretion, digestion, absorption and excretion, but also, very importantly, defence. The gastrointestinal tract acts not only as a barrier to harmful materials and pathogens but also contains the vast number of beneficial bacterial populations that make up the microbiota. Communication between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 107 publications
(141 reference statements)
2
83
2
3
Order By: Relevance
“…In general, histological studies have also shown an age-related thinning of the human olfactory epithelium [26,27]. In contrast, observations in the age-associated changes in the architecture of the intestinal epithelium have not been consistent [28].…”
Section: Discussionmentioning
confidence: 95%
“…In general, histological studies have also shown an age-related thinning of the human olfactory epithelium [26,27]. In contrast, observations in the age-associated changes in the architecture of the intestinal epithelium have not been consistent [28].…”
Section: Discussionmentioning
confidence: 95%
“…It is controversial whether age-related dysmotility is due to a decrease in the amount of smooth muscle cells themselves or to damage to intermediate cells such as neurons and ICCs. [45][46][47][48] ICCs play an important part in colonic motility: propulsion is considered to be induced by ICCs in the submucosal plexus, and the ICCs in muscle layers are thought to mediate between the nerves and the smooth muscle cells. 49 According to a previous human study and the present study, the concentration of ICCs seems to decrease in old age.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, there is a progressive loss of intestinal homeostasis leading to impaired function and a higher probability of developing diseases such as cancer. One of the reasons for the loss of tissue homeostasis in mammals is speculated to be an altered stem cell behavior (Kirkwood, 2004;Saffrey, 2014); however, the exact effects of aging on the number and function of intestinal stem cells remains largely unclear. In recent years, Drosophila has become a prominent model organism to study mechanisms of regeneration and aging in the intestine (Jasper, 2015).…”
Section: Introductionmentioning
confidence: 99%